2017
DOI: 10.1007/s40256-017-0245-0
|View full text |Cite|
|
Sign up to set email alerts
|

Comparative Efficacy of Drugs for Preventing Acute Kidney Injury after Cardiac Surgery: A Network Meta-Analysis

Abstract: Natriuretic peptide is probably the preferred pharmacologic strategy to prevent AKI in adult patients undergoing cardiac surgery, especially in those at high risk of AKI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
14
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 95 publications
2
14
0
Order By: Relevance
“…For example, a recent trial by Turner and colleagues [15] examined the role of perioperative sodium bicarbonate infusion in preventing AKI after cardiothoracic operations; however, this study was terminated due to lack of efficacy. A recent network meta-analysis of randomized trials that examined the effect of different drugs in preventing AKI found that natriuretic peptide has the largest effect size in preventing AKI compared with other drugs, including steroids, statin, erythropoietin, fenoldopam, dexmedetomidine, levosimendan, N-acetylcysteine, and sodium bicarbonate [16].…”
Section: Hospitalization Cost and Health Care Expenditurementioning
confidence: 99%
“…For example, a recent trial by Turner and colleagues [15] examined the role of perioperative sodium bicarbonate infusion in preventing AKI after cardiothoracic operations; however, this study was terminated due to lack of efficacy. A recent network meta-analysis of randomized trials that examined the effect of different drugs in preventing AKI found that natriuretic peptide has the largest effect size in preventing AKI compared with other drugs, including steroids, statin, erythropoietin, fenoldopam, dexmedetomidine, levosimendan, N-acetylcysteine, and sodium bicarbonate [16].…”
Section: Hospitalization Cost and Health Care Expenditurementioning
confidence: 99%
“…In recent years, a variety of preventive measures has been suggested to reduce the incidence of AKI, among which the greatest potential is found in the administration of natriuretic peptide, fenoldopam and dexmedetomidine. [14] For example, Mamoulakis et al…”
Section: Discussionmentioning
confidence: 99%
“…These trials, which enrolled nearly 1000 patients, found a significantly decreased incidence of postoperative AKI in patients who received natriuretic peptides. 51 , 62 , 63 A meta-analysis of RCTs performed in patients undergoing cardiac surgery and other major surgery indicated that fenoldopam led to a lower risk of AKI, but not RRT or death. 64 However, these studies also had small sample sizes and were of variable quality.…”
Section: Intraoperative Measuresmentioning
confidence: 99%
“… 65 Meta-analyses of small sized RCTs concluded that levosimendan resulted in a significant decrease in the incidence of AKI after cardiac surgical procedures. 63 , 66 , 67 However, the 2 largest RCTs conducted to date, failed to report any beneficial effects of levosimendan in preventing severe AKI (defined as need for RRT) in patients undergoing cardiac surgery. 68 , 69 …”
Section: Intraoperative Measuresmentioning
confidence: 99%